2021
DOI: 10.4149/bll_2021_100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standard prophylactic and preemptive therapeutic low molecular weight heparin treatments in hospitalized patients with COVID-19

Abstract: INTRODUCTION: Anticoagulant treatment approach in patients with COVID-19 is not well studied and not standardized. We aimed to compare the effects of standard prophylactic and pre-emptive therapeutic Low-Molecular-weight Heparin (LMWH) treatment approaches on mortality in patients with COVID-19. PATIENTS AND METHODS: This retrospective and single-centre study includes patients aged ≥ 18 years, who were diagnosed with COVID-19 and treated with LMWH during the hospital stay. Therapeutic dose of LMWH was defi ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…After excluding duplicates and out-of-scope articles based on title/abstract, 349 potentially eligible records for inclusion were selected for full-text reading. After full-text reading, 318 articles were excluded, leading to the inclusion of 31 eligible studies 1848 (6 RCTs and 25 cohort studies) with a total of 11,430 COVID-19 patients (Table 1). Only hospitalized patients were included in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates and out-of-scope articles based on title/abstract, 349 potentially eligible records for inclusion were selected for full-text reading. After full-text reading, 318 articles were excluded, leading to the inclusion of 31 eligible studies 1848 (6 RCTs and 25 cohort studies) with a total of 11,430 COVID-19 patients (Table 1). Only hospitalized patients were included in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 . A total of 7 studies reported data for intermediate versus prophylactic dose [ 11 , 27 , 28 , 29 , 30 , 34 , 35 ], while 17 studies reported data for therapeutic versus prophylactic dose of thromboprophylaxis [ 12 , 23 , 24 , 25 , 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Three studies contributed data for both intermediate versus prophylactic and therapeutic versus prophylactic dose analyses [ 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations